Copper(II)-induced fluorescence quenching of a BODIPY fluorophore - Herten, Dirk-Peter; Haderspeck, Andreas; Braun, Felix; Wadepohl, Hubert (Zeitschrift für anorganische und allgemeine Chemie, 2018)
The ongoing developments in fluorescence microscopy have pushed the interest in new fluorescent probes with specific properties. Aside of controlling emissive states by light irradiation, defined control by changing the chemical environment has come into focus. In this context, we designed a fluorescent probe by conjugation of bipyridine, acting as sensor for CuII, to a BODIPY derivative at the shortest possible distance between sensor and chromophore. Herein, we present the synthesis of the BODIPY probe along with its crystal structure. We found a strong dependence of absorption and emission upon CuII complex formation decreasing the fluorescence quantum yield to ca. 1 % in respect to the pure probe. We hypothesize that further functionalization with a linker could make this compound and interesting probe for fluorescence microscopy.